1999
DOI: 10.22358/jafs/68810/1999
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of blood plasma growth hormone levels in young dairy and beef cattle

Abstract: The characteristics of the growth hormone (GH) secretion pattern in the peripheral blood plasma of young dairy and beef cattle were described. Ten Black and White (BW) and nine Piemontese cattle of both sexes, aged 11 months, were tested. The blood was sampled through catheters at 15-min intervals over a period of 4 h. The GH concentration was determined by double antibody radioimmunoassay. Pulse characteristics of GH were calculated using the PULSAR program. The results obtained confirmed the pulsatile nature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Our previous study (Grochowska et al, 1999) showed significantly higher GH secretion parameters in young Friesian heifers and bulls than in Piemonteses. Kazmer et al (1986) also reported that in Holstein cows selection for high milk yield resulted in a greater GH serum concentration in contrast to the level observed in cows selected for low milk yield or to control animals.…”
Section: Discussionmentioning
confidence: 76%
“…Our previous study (Grochowska et al, 1999) showed significantly higher GH secretion parameters in young Friesian heifers and bulls than in Piemonteses. Kazmer et al (1986) also reported that in Holstein cows selection for high milk yield resulted in a greater GH serum concentration in contrast to the level observed in cows selected for low milk yield or to control animals.…”
Section: Discussionmentioning
confidence: 76%